2020
DOI: 10.1101/2020.06.04.133892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linear-Nonlinear Cascades Capture Synaptic Dynamics

Abstract: Synaptic dynamics differ markedly across connections and strongly regulate how action potentials are being communicated. To model the range of synaptic dynamics observed in experiments, we develop a flexible mathematical framework based on a linear-nonlinear operation. This model can capture various experimentally observed features of synaptic dynamics and different types of heteroskedasticity. Despite its conceptual simplicity, we show it is more adaptable than previous models. Combined with a standard maximu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“…5.Ai). Such a dependence between the number of intra-burst spikes and the changes in synaptic efficacy is observed in experiments (36). Since the probability of observing N subsequent events with short ISIs decreases as N increases this allows post-synaptic cells to better distinguish events from bursts, regardless of the overlap between IEI and IBI interval distributions.…”
Section: Burst Length and Low Event Ratesmentioning
confidence: 71%
See 1 more Smart Citation
“…5.Ai). Such a dependence between the number of intra-burst spikes and the changes in synaptic efficacy is observed in experiments (36). Since the probability of observing N subsequent events with short ISIs decreases as N increases this allows post-synaptic cells to better distinguish events from bursts, regardless of the overlap between IEI and IBI interval distributions.…”
Section: Burst Length and Low Event Ratesmentioning
confidence: 71%
“…For the decoding cells, we adopted the model described in Ref. (36), that defines STP weight functions as a composition of a linear filtering and nonlinear function. This can be formalized as…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, these factors influence the interaction between the pre-and postsynaptic neurons which cannot be captured by the dynamics of STP solely. It was suggested that alternative models of plasticity with less biophysical constraints like generalized bilinear model ( 16) and linear-nonlinear cascade model (18) could provide more flexible representation of STP dynamics compared to the TM model. Despite such limitations, the conventional three-parameter TM model is sufficient to describe STP in many cases (13).…”
Section: Discussionmentioning
confidence: 99%
“…Ghanbari et al (16,17) also used a different GLM to directly estimate the STP dynamics, a model that can be considered as an alternative to the TM model. Rossbroich et al (18) introduced a new synaptic model which represents short-term dynamics by combining an exponential kernel with a non-linear readout function. The simplicity of this model enabled applying the concepts of STP in artificial neural networks to examine its role in learning.…”
Section: Introductionmentioning
confidence: 99%
“…A wrong short-term plasticity model will therefore lead to a wrong connectivity in the circuit. Here, it will be interesting to see how a more expressive model of short-term plasticity [62] influences the optimal circuit structure. Finally, of course, our optimality assumption could be wrong to different degrees.…”
Section: Discussionmentioning
confidence: 99%